Short Communication: Utilization of Vegetables Waste as Carbon Source in Cultivation Medium for Daphnia sp. - Reni Anggraini; Andri Kurniawan; Ahmad Fahrul Syarif (BERITA BIOLOGI, 2022)
Daphnia sp. is one of the most important natural feeds in freshwater fish farming sector. Daphnia contain considerably high protein, easy to be cultivated, short harvest time, the size is appropriate to the fish's mouth size, its movement can stimulate fish larvae to eat it, does not pollute the aquatic environment or larval rearing media and can be enriched with certain ingredients. Carbon is a source of energy for the growth of Daphnia directly or through microorganisms that become feed for Daphnia. This study aimed to analyze the effect of providing vegetable waste as a carbon source on the abundance of Daphnia and determine the best type of vegetable waste for the cultivation of Daphnia. The research method was an experimental method using 3 (three) different vegetables, namely spinach, mustard greens, and cabbage. The study was conducted using a completely randomized design with 4 (four) treatments in the form of different vegetables and control and the test sample was repeated 3 (three) times. The growth of Daphnia was observed for 16 days of cultivation time. The results showed that the provision of vegetables affected the population growth of Daphnia. Spinach (P3) was the treatment with the highest growth value, which average growth was sebanyak 96,67 individual (ind) of Daphnia with a specific growth rate of 0.055%. The temperature in Daphnia culture media generally ranged from 25-27℃, while the pH in Daphnia culture media showed a value of 7.4-9.5. The results of PCA analysis showed that water temperature was a variable that was strongly correlated with the growth of Daphnia.